Spatial and spatiotemporal econometrics - LeSage, James P.; Pace, R. Kelley (Amsterdam ; Oxford : Elsevier JAI, 2004)
This volume focuses on spatial and spatiotemporal econometric models, with contributions that detail estimation and inference for these models. Contributions outline estimation, inference and model comparison using maximum likelihood, Bayesian and hierarchical Bayes, instrumental variables, generalized method of moments, maximum entropy, non-parametric and space-time panel approaches.
Includes bibliographical references.
Keywords: Space in economics -- Econometric models; Space in economics -- Mathematical models; Time and economic reactions -- Econometric models